(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This is an edited and corrected version of the interview given on August 23, 2022, by Adrian Kohler and Basil Jones, founders of the South African company Handspring Puppet Company to Mario Piragibe for the 4th Meeting Poetics of the Inanimate, organized by the Research Group: Scenic Poetics: Visual and Performative (CNPq). The conversation addresses some of the main moments of the company’s more than 30-year career, with highlights for the productions War Horse and Walk with Amal, motivated by discussions about the discursive power of puppet construction and puppet theater as a tool for creation of animal protagonists without the need to humanize them.